Supraspinal, spinal, and motor unit adjustments to fatiguing isometric contractions of the knee extensors at low and high submaximal intensities in males - Angius, Luca; Del Vecchio, Alessandro; Goodall, Stuart; Thomas, Kevin; Ansdell, Paul; Atkinson, Elliot; Farina, Dario; Howatson, Glyn (Journal of Applied Physiology, 2024)
Contraction intensity is a key factor determining the development of muscle fatigue, and it has been shown to induce distinct changes along the motor pathway. The role of cortical and spinal inputs that regulate motor unit (MU) behavior during fatiguing contractions is poorly understood. We studied the cortical, spinal, and neuromuscular response to sustained fatiguing isometric tasks performed at 20% and 70% of the maximum isometric voluntary contraction (MVC), together with MU behavior of knee extensors in healthy active males. Neuromuscular function was assessed before and after performance of both tasks. Cortical and spinal responses during exercise were measured via stimulation of the motor cortex and spinal cord. High-density electromyography was used to record individual MUs from the vastus lateralis (VL). Exercise at 70%MVC induced greater decline in MVC (P = 0.023) and potentiated twitch force compared with 20%MVC (P < 0.001), with no difference in voluntary activation (P = 0.514). Throughout exercise, corticospinal responses were greater during the 20%MVC task (P < 0.001), and spinal responses increased over time in both tasks (P ≤ 0.042). MU discharge rate increased similarly after both tasks (P ≤ 0.043), whereas recruitment and derecruitment thresholds were unaffected (P ≥ 0.295). These results suggest that increased excitability of cortical and spinal inputs might be responsible for the increase in MU discharge rate. The increase in evoked responses together with the higher MU discharge rate might be required to compensate for peripheral adjustments to sustain fatiguing contractions at different intensities.NEW & NOTEWORTHY Changes in central nervous system and muscle function occur in response to fatiguing exercise and are specific to exercise intensity. This study measured corticospinal, neuromuscular, and motor unit behavior to fatiguing isometric tasks performed at different intensities. Both tasks increased corticospinal excitability and motor unit discharge rate. Our findings suggest that these acute adjustments are required to compensate for the exercise-induced decrements in neuromuscular function caused by fatiguing tasks.
CRIS-Team Scopus Importer:2024-06-28
Keywords: exercise; fatigue; high-density EMG; motor unit; transcranial magnetic stimulation